Neural Correlates of Autobiographical Memory: Evidence From a Positron Emission Tomography Study in Patients With Mild Cognitive Impairment and Alzheimer's Disease - Frankenberg, Claudia; Pantel, Johannes; Haberkorn, Uwe; Degen, Christina; Buchsbaum, Monte S.; Herold, Christina J.; Schröder, Johannes (Frontiers in Psychiatry, 2021)
Background: Autobiographical memory (AM) changes are the hallmark of Alzheimer’s disease (AD) and Mild Cognitive Impairment (MCI). In recent neuroimaging studies, AM changes were associated with numerous cerebral sites, such as the frontal cortices, the mesial temporal lobe, or the posterior cingulum. Regional glucose uptake in these sites was investigated for underlying subdimension using factors analysis. Subsequently, the factors were examined with respect to AM performance in a subgroup of patients. Methods: Data from 109 memory clinic referrals were analysed, who presented with MCI (n = 60), mild AD (n = 49), or were cognitively intact. Glucose metabolic rates determined by positron-emission tomography with 18F-fluorodeoxyglucose in 34 cerebral sites important for AM were investigated for underlying subdimensions by calculating factor analysis with VARIMAX rotation. Subsequently, the respective factor scores were correlated with episodic and semantic AM performance of 22 patients, which was measured with a semi-structured interview assessing episodic memories (characterized by event-related emotional, sensory, contextual, and spatial-temporal details) and personal semantic knowledge from three periods of life (primary school, early adulthood, and recent years). Results: Factor analysis identified seven factors explaining 69% of the variance. While patients with MCI and AD showed lower values than controls on the factors frontal cortex, mesial temporal substructures and occipital cortex, patients with MCI presented with increase values on the factors posterior cingulum and left temporo-prefrontal areas. The factors anterior cingulum and right temporal cortex showed only minor, non-significant group differences. Solely the factor mesial temporal substructures were significantly correlated with both, episodic memories (r = .424, p < .05) and personal semantic knowledge (r = .547, p < .01) in patients with MCI/AD. Conclusions: The factor structure identified corresponds by large with the morphological and functional interrelations of the respective sites. Interestingly, changes of the mesial temporal substructures were correlated with both semantic and episodic AM. Our findings suggest that AM deficits do not only reflect neurodegenerative changes but also refer to compensatory mechanisms as they involve both quantitative losses of specific memories and qualitative changes with a semantization of memories.